Changes in the Microbial Community Structure and Soil Chemical Properties of Vertisols Under Different Cropping Systems in Northern China - Song, Xiuli; Tao, Bo; Guo, Jing; Li, Jingjing; Chen, Guofeng (Frontiers in Environmental Science, 2018)
The cropping system changes the soil physical and chemical properties and directly influences the microbiome composition and diversity. Microflora are important drivers of the nutrient cycling process and can affect soil fertility, plant productivity and environmental sustainability. Here, the soil fertility and microbial community changes in four soybean-containing plant systems were studied for 12 years. Amplification sub-sequencing techniques were used to assess the differences in the soil community structure under different cropping systems and identified significant positive and negative fertility factors. The lowest effective P, Cu and Mn contents were obtained with the fallow-soybean planting mode. The soybean continuous cropping pattern yielded significantly increased effective organic matter (OM), significantly higher N, K, Mn and Fe contents and a lower effective P content. The wheat-soybean rotation cropping pattern produced the highest effective P and Cu contents and significantly lower OM and effective N and Fe contents, whereas the corn-soybean rotation planting system yielded the highest pH and significantly lower K and Zn contents (P<0.05). Different cropping systems yielded microbial communities with significant differences in diversity and relative abundances. Significantly higher microbial diversity was observed with the fallow-soybean planting mode, which showed significantly higher relative abundances of Chloroflexi, Verrucomicrobia, Nitrospirae and Bacteroidetes and a significantly lower relative abundance of Actinobacteria. The soybean continuous cropping pattern yielded significantly higher relative abundances of Proteobacteria, Bacteroidetes, and Actinobacteria and significantly lower relative abundances of Acidobacteria and Planctomycetes, whereas the wheat-soybean rotation cropping pattern generated significantly higher relative abundances of Planctomycetes, Gemmatimonadetes, candidate division WPS-1 and Armatimonadetes compared with the other planting systems. The fungi in all the samples were mainly distributed in Ascomycota, Basidiomycota and Zygomycota, and these groups reached relative abundances as high as 90%. The wheat-soybean rotation cropping pattern produced a significantly higher relative abundance of Ascomycota, and the fallow-soybean planting mode yielded a significantly higher relative abundance of Zygomycota. An extremely low soil fertility index greatly affects the microbial community structure, and the effective P, Cu, Mn, and K contents of black soil are environmental factors closely related to microbial diversity. These findings are of great significance for protecting the ecological environment.